THE USE OF ICT IN CLIL-BASED TEACHING OF PEDAGOGY AND METHODOLOGY IN HIGHER EDUCATION - Gunay Shiraliyeva (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This article examines the specifics of teaching pedagogical subjects in English using CLIL and ICT. It also analyzes the impact of digital technologies on the development of students’ professional and communicative competencies in higher education.